The impact of annotation on concrete and abstract visual representations in science education: testing the expertise reversal effect - Robert Zheng; Holly Cordner; Jeffrey Spears (The Asia-Pacific Society for Computers in Education (APSCE), 2022)
Abstract This study investigates the effects of annotation on abstract and concrete visual representations in science education. Two studies were conducted: Study 1 investigated the interaction between annotation and visual representations. The results of this study demonstrated that in science learning, annotation with abstract visual representations was superior to annotation with concrete visual representations. Study 2 tested the expertise reversal effect in a three-factor design where the interaction among annotation, visual representation, and prior knowledge was measured. The findings showed that high-prior-knowledge learners performed better in the annotation-abstract visual condition than in the annotation-concrete visual condition where low-prior-knowledge learners showed the opposite outcome-confirming that the expertise reversal effect is at play in how science learners utilize visual information. The study has clarified the roles of prior knowledge, visual representation, and instructional strategy on learner cognitive processing in science education. This knowledge should prove useful for educators as they engage in the design and development of computer-based science learning.